Chemotherapy-induced cellular senescence promotes stemness of aggressive B-cell non-Hodgkin’s lymphoma via CCR7/ARHGAP18/IKBα signaling activation - Yangyang Wang; Fan Wu; Yang Wan; Huiping Wang; Linhui Hu; Qianshan Tao; Zhimin Zhai; Jiyu Wang; Keke Huang; Anwen Ren; Jinlan Li; Liuying Yi; et al. (Journal for ImmunoTherapy of Cancer)
Background Resistance to existing therapies is a major cause of treatment failure in patients with refractory and relapsed B-cell non-Hodgkin’s lymphoma (r/r B-NHL). Therapy-induced senescence (TIS) is one of the most important mechanisms of drug resistance.Methods This study used single-cell RNA sequencing to analyze doxorubicin-induced senescent B-NHL cells. C-C chemokine receptor 7 (CCR7) expression in patients with aggressive B-NHL was assessed using immunohistochemistry and flow cytometry. Lentiviral transfection was used to target CCR7 expression in Raji and SU-DHL-2 cells. Protein localization was visualized through immunofluorescence, while western blotting and co-immunoprecipitation were used to analyze protein expression and interactions. Cell proliferation was measured with the Cell Counting Kit-8 assay, and senescent cells were detected using senescence-associated β-galactosidase staining. The stemness of cells was evaluated through colony and sphere formation assays. Transwell assays assessed cell migration and invasion. Finally, inhibitors GS143 and Y27632 were used to examine the effect of IKBα and ARHGAP/RhoA inhibition on B-NHL-TIS.Results Here we identified a distinct group of TIS, composed of memory B-cell population characterized by strong positive expression of CCR7, which was significantly elevated in TIS population compared with normal proliferating and autonomously senescent lymphoma cell populations. Additionally, CCR7 expression was significantly upregulated in patients with r/r B-NHL, and was an independent prognostic factor in B-NHL, with high CCR7 expression being strongly associated with poor prognosis. In vitro results indicated that CCL21 induced migration and invasion of B-NHL cells via CCR7, while blocking CCR7 reduced doxorubicin-induced migration and invasion of these cells. Furthermore, B-NHL-TIS regulated by CCR7 and exhibited enhanced phenotypic and functional stemness features, including the upregulation of stemness markers, increased colony-forming, invasive and migratory capabilities. Mechanistically, blocking CCR7 reversed the stemness characteristics of senescent B-NHL cells by inhibiting the activation of ARHGAP18/IKBα signaling.Conclusions Together, TIS promotes the stemness of B-NHL cells via CCR7/ARHGAP18/IKBα signaling activation and targeting CCR7/ARHGAP18 might overcome the chemoresistance of senescent B-NHL cells by inhibiting stemness acquisition and maintenance.